Pengaruh Inovasi, Promosi, Harga, Kualitas Pelayanan, Dan Lokasi Terhadap Keputusan Pembelian Studi Kasus Pada Konsumen Drw Skincare Di Mulyojati Metro Barat - Suryadi, Suryadi; Septiana, Nani; Maryuni, Peti Ninda (Jurnal Manajemen DIVERSIFIKASI, 2023)
This study was conducted to determine the effect of Innovation, Promotion, Price, ServiceQuality and Location on purchasing decisions for DRW Skincare consumers in WestMulyojati Metro. The type of research used is quantitative research. The sampling techniqueused was purposive sampling. Only 71 samples used were in accordance with predeterminedcriteria. The data used is primary data with the distribution of questionnaires in the form of alist of questions with several alternative answers for respondents. The statistical test used totest the hypothesis is multiple linear regression analysis and tested using the statisticalpackages for the social science (SPSS) version 25 program. Based on the results of statisticaltests, it shows that innovation, promotion, service quality and location have a positive andsignificant influence on purchasing decisions for DRW Skincare consumers in West MulyojatiMetro, while price has no and significant effect on purchasing decisions for DRW Skincareconsumers in West Mulyojati Metro.